Bitter taste receptor-guided delivery of limonin: Bridging taste masking and gut health - Wei-yun Zhang; Jin-song Liao; Jun-ru Qi (Trends in Food Science & Technology, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Integrated transcriptomic and metabolomic analyses reveal the involvement of AtGASA1 and AtGASA4 in salicylic acid pathway-associated immune responses in Arabidopsis - Jian-Bo Song; Ya-Ru Li; Zi-Xin Zhao; Xian-Zhi Zuo; Cai-Feng Wang; Min Huang; Shu-Fan Liu; Yu-Fan Chen; Wen-Qian Song; Lin Wang; Ying-Juan Wang; Xuan Huang (Plant Science, 2026)

Copper and zinc isotopes reveal redox-driven nutrient cycles in the Mesoproterozoic ocean - Kexin Song; Dandan Li; Chengshuai Yuan; Yang Liu; Yuan-Ru Qu; Sheng-Ao Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Evolution of lipid profiles, microbiota succession, and potential warmed-over flavor markers in prepared squid (Dosidicus gigas) during extended refrigerated storage: A multi-omics study - Xin Zhang; Rui Tan; Chengxin Lv; Zhiyuan Xiao; Kang Guo; Bin Zhang; Ru Song; Yan Xu; Wei Xia (Food Bioscience, 2026)

Effects of long-term exposure to 2,6-di-tert-butylhydroxytoluene and its transformation product 2,6-di-tert-butylbenzoquinone on development and reproduction in zebrafish - Ze Li; Junya Song; Liqiang Yang; Yufeng Gong; Shaoguo Ru; Weiwei Wang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Novel temperature-tolerant Schiff base derivative as high-efficiency inhibitor for acid corrosion of N80 steel - Li-Mao Chen; Shuang-Jian Li; Ru-Han Li; Bo-Kai Liao; Xing-Peng Guo; Long-Fei Song (Chemical Engineering Journal, 2026)

Sublethal cinnamon essential oil induces oxidative stress-driven metabolic reprogramming and attenuates spoilage potential in Psychrobacter faecalis - Yueping Yang; Ru Song; Pengcheng Li; Ye Tao; Xiaoyu Zou; Yan Xu; Rongbian Wei (Food Research International, 2026)

Microbial and environmental determinants of 1-propanol biosynthesis in Jiang-flavor Baijiu fermentation - Wei-Tao Zhai; Han Zhao; Li-Juan Chai; Wei Zhang; Xiao-Juan Zhang; Zhen-Ming Lu; Chuan-Qiang Gao; Guan-Ru Si; Wen-Qing Zhang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Microbiology, 2026)

Heterolytic urea exchange-mediated thermal locking: Architecting 3D printed photo-mechanochromic smart elastomers - Min Yu; Yeting Huang; Dong Wang; Ru Song; Hanzhao Gong; Shuming Zhang; Xiaoyu Han; Yangzheng Li (Chemical Engineering Journal, 2026)

Quercetin restores oocyte maturation and embryo development in DEHP-exposed mice via mitochondrial protection and apoptosis inhibition - Dui Sun; Qi Yang; Zhi-Hui Gong; Meng-Lei Feng; Zhi-Wen Jia; Bin-Shuo Yang; Zhao-Yu Jiang; Chun-Ru Song; Fang-Rui Xue; Xiao-Jie Zhang; Hao-Yang Zhang; Chun-Lan Zhang; et al. (Chemico-Biological Interactions, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Activation-optimized anti-CD3 valency control enables combinatorial discovery of multi-specific nanoantibodies for solid tumor immunotherapy - Long Zhu; Ya-Jing Ma; Jian-Kang Kang; Xiu-Hai Che; Dong-Kun Zhao; Yin-Yi Cai; Yao-Ru Yu; Song Shen; Jun Wang (Science Bulletin, 2026)

Phytohormonal orchestration of plant phosphate starvation responses - Kai-Kai Lu; Ru-Feng Song; Yu-Pu Fan; Ling-Yu Xu; Bo-Hao Chen; Shu-Xian Li; Meng-Tian Sun; Guo-Mao Liu; Xiao-Li Huang; Lin Li; Xin-Ru Guo; Feng Ren; et al. (Journal of Plant Physiology, 2026)

Health Benefit Assessment of Continuous Improvement of Air Quality Action Plan in China - Weiming An; Hongtao Mao; Xiaoda Xue; Xiaoqian Cai; Xin Song; Pengbo Wang; Yongle Liu; Hongyu Ji; Jianbo Ru; Lei Zhang (Environmental Pollution, 2026)

PdPI, a PISTILLATA ortholog from Populus davidiana, enhances drought tolerance by regulating stomatal aperture and antioxidant defense - Siyuan Li; Meiqi Lu; Ling Jin; Zhanchen Ren; Xinyu Wang; Song Chen; Yunxia Wei; Jiaxin Liu; Yuanfu Liu; Haoran Bao; Yue Zhang; Tingyu Cao; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Foc4-Ap1, a putative aspartic protease of Fusarium oxysporum f. sp. cubense race 4, targets banana NAD(P)H-quinone oxidoreductase subunit S to promote virulence - Ru-Jing Zeng; Wen-Jing Chen; Zheng Li; Huan-Cai Ou; Qing-Dong Chen; Mei Luo; Han-Da Song; Zhang-Yong Dong (Physiological and Molecular Plant Pathology, 2026)

Dual-engineered defect-rich molecularly imprinted zirconium metal organic framework platform for selective adsorption and ultrasensitive analysis of alternariol - Shi-Rong Sun; Lu Liu; Xia Wang; Yan Dong; Yan Li; Qianyun Sun; Yanfang Zhao; Xiangfeng Chen; Yong-Ning Wu; Rabah Boukherroub; Ru-Song Zhao (Journal of Hazardous Materials, 2026)

Low kinetic perturbation by the rapidly advancing ice-water interface suppresses Na+/Cl− induced myofibrillar protein network assembly - Yajin Zhang; Ziaur Rahman; Hongwei Song; Shanbai Xiong; Tao Yin; Ru Liu; Juan You (Food Chemistry, 2026)

Persimmon tannin: a novel green enhancer for dual improvement of texture and digestibility in surimi gels - Jingzhi Yan; Shiren Zhang; Kaile Chen; Yanxu Zhuang; Yiyi Cheng; Yan Xu; Ru Song; Haiyan Gao (Food Chemistry, 2026)

Ratio limitation of burnt-bitter-aroma compounds in strong-aroma Baijiu - Qing-Ru Liu; Shun-Hua Zhang; Zheng-Juan Zhu; Jing Luo; Ling Xiang; Yan-Hong Xiang; Song-Tao Wang; Wen-Wen Zhang; Qing-Qing Liu; Ting Huang; Zheng-Hong Xu; Yong-Jun Yuan (Food Chemistry, 2026)

Rhizosphere microbial diversity and inoculation potential for the endangered opisthopappus taihangensis - Yanyan Han; Lihui Zhang; Qiantong Ru; Juan Song; Bianxia Bai; Shan Jin; Jiahong Ren (Plant and Soil, 2026)

Genome wide association analysis and association of genetic risk and lifestyle with upper gastrointestinal cancer among an endoscopy-screened cohort in China - Feifan He; Xianhui Ran; Hao Jiang; Zhiyuan Fan; Yueying Zhang; Jinwu Wang; Changqing Hao; Guohui Song; Yanwei Gong; Yanyan Li; Xinqing Li; Ru Chen; et al. (Science Bulletin, 2026)

Green manure co-application boosts arid agroecosystem sustainability: Mixed sowing of feed rape and hairy vetch modulates N input and enzymes for optimized wheat production - Ru Yu; Jie Zhou; Fangdi Chang; Jiashen Song; Jing Wang; Xiaobin Li; Hua Zhang; Jufeng Cao; Xiaohong Li; Hanjiang Liu; Hongyuan Zhang; Yuyi Li (Field Crops Research, 2026)

Rational design of one-dimensional chain-like metal-organic frameworks featuring engineered nano-pockets for highly selective and efficient uranium sequestration - Zhi Wu; Shu-Yuan Zhang; Bin Lin; An-Min Song; Fei-Yi Kong; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2026)

A novel dual-function biosensor based on polarity reversal of MFC for bioelectricity generation and detecting trimethylamine-N-oxide - Sheng-chao Gao; Yu-xuan Wang; Yong-dong Li; Ru-meng Zhang; Ya-nan Zhang; Jin-song Dong; Hong-xia Ni; Yi Chen; Xi-hui Shen; Ying Liu (Chemical Engineering Journal, 2026)

Multifunctional carboxymethyl cellulose/polydopamine dual-network conductive hydrogels for motion detection and photothermal therapy - Yiying Wei; Bo Cong; Xiaopu Ji; Dangyang Wang; Jinghui Hu; Zonglei Mou; Haiqing Song; Yue Zhi; Yushu Liu; Guofeng Zhang; Wan Ru Sun; Pingyu Wang; et al. (Carbohydrate Polymers, 2026)

AtGASA1 positively regulates Arabidopsis response to salt stress by suppressing accumulation of reactive oxygen species - Jian-Bo Song; Hao-En He; Cai-Feng Wang; Xian-Zhi Zuo; Zi-Xin Zhao; Ya-Ru Li; Yu-Fan Chen; Shu-Fan Liu; Han-Wen Guo; Xuan Huang (Plant Cell Reports, 2026)

Study of enhancing analgesic potential of μ-conotoxins from the computational and pharmacological insights - Fan Zhao; Yunxia Liu; Ying Cui; Yushan Ding; Liu Ru; Ting Meng; Hongtao Yang; Yongbo Song (Molecular Diversity, 2026)

Multi-system geochronometer constraints on thermo-tectonic evolution of the Qiangtang Terrane, central Tibetan Plateau: Comment - Xiao-Long Song; Ru-Ye Tian; Kang-Yu Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Insights into frozen quality preservation and energy conservation of salted swamp eel (Monopterus albus) fillets - Hongwei Song; Yajin Zhang; Hong Yang; Ru Liu; Tao Yin; Liu Shi; Juan You (International Journal of Refrigeration, 2026)

Multi-channel carbon nanofibers with enhanced ion diffusion and ultra-stability for flexible supercapacitors at commercial-scale mass loading - Guangjie Yang; Yulong Yang; Jian Song; Zhenye Yin; Qian Zhang; Zhenlu Liu; Haoqi Yang; Min Ru; Shaochun Tang; Shuijian He (Chemical Engineering Journal, 2026)

Anti-discoloration of Tuna Fillet Through the Lactic Acid Bacteria Treatment: Interpretation by Metabolomic Analysis - Du-Min Jo; Mi-Ru Song; Yoon Cho; Kyung-Jin Cho; Seul-Ki Park; Young-Mog Kim (Probiotics and Antimicrobial Proteins, 2026)

Recent understanding of crosstalk between muscle and different organs in regulating freshwater fish flesh quality under stress condition: A review - Liwen Wu; Liangzi Zhang; Ling Peng; Yong Long; Guili Song; Soottawat Benjakul; Juan You; Ru Liu; Qilin Huang; Huawei Ma; Dan Jia; Tao Yin (Aquaculture, 2026)

The role of artificial intelligence in advancing population-based cancer registration - Shuai Ding; Mingyuan Liu; Hao Wang; Cheng Song; Luyue Zhao; Zhihao Yang; Yue Wang; Yifan Wang; Haitao Cui; Zihao Liu; Dongrun Liu; Tomohiro Matsuda; et al. (Science Bulletin, 2026)

Lactic acid modulates empty-cup aroma persistence in Baijiu via molecular interaction mechanisms: a case study of strong-aroma and soy-sauce-aroma Baijiu - Qing-Ru Liu; Shun-Hua Zhang; Xiao-Juan Zhang; Zheng-Juan Zhu; Ru-Yi Li; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Guan-Yu Fang; Qing-Qing Liu; Yong-Jun Yuan; et al. (Food Chemistry, 2026)

Naphthalene versus benzene donor in vinyl-linked donor–π–acceptor COFs: Dueling for photocatalytic H2O2 production and water purification - Tong Chen; Meng Xie; Wenli Wu; Xiangfeng Chen; Lingxi Zhao; Ru-Song Zhao (Chemical Engineering Journal, 2026)

Side-chain modified covalent organic frameworks for enhanced visible light photocatalytic degradation of bisphenol A and application in seawater - Tianshuo Liu; Jing Sun; Meng Xie; Ru-Song Zhao (Chemical Engineering Journal, 2026)

Beyond electrostatic interaction: Ball milling-induced dominance of pore filling and π-π stacking for methylene blue adsorption on tobacco stem derived activated carbon - Dong-Can Lv; Meng-Ru Chen; Mei-Rong Song; Guang-Ce Jiang; Zhi-Min Wang (Journal of Water Process Engineering, 2026)

Autophagy, ROS, and their interplay in plant adaptive responses - Chi Zhang; Song-Qi Li; Pengwei Jing; Run-Xin Wu; Yu-Qing Ma; Ji-Xiao Wu; Ru-Feng Song; Wen-Cheng Liu (Journal of Plant Physiology, 2026)

Straw interlayer burial improved soil humic fractions via pore-microbe mediated life strategy hierarchy regulating pore structure and bacterial characteristic in saline soils - Hongyuan Zhang; Jiashen Song; Jie Zhou; Fangdi Chang; Ru Yu; Wenhao Feng; Haoruo Li; Jing Wang; Xiaobin Li; Yuyi Li (Journal of Environmental Management, 2026)

Modulating limonin release via pectin fine structure in Ca2+-citrus pectin emulsion gels - Wei-yun Zhang; Jin-song Liao; Jun-ru Qi (Food Research International, 2026)

Synthetic microalgae community promotes chili growth planted in waste stone powder by enriching beneficial root endophytic bacteria and fungi - Cong Liu; Hongqing Wei; Shaoguo Ru; Weizhong Wang; Zhengmao Li; Lijuan Liu; Xiukai Song; Jun Wang (Plant and Soil, 2026)

Prediction Of Relative Permeability Curve Based On Machine Learning Driven By Logging Data - Jia-ru Zou; Shou-dong Huo; En-liang Liu; Tong-sheng Zeng; Lian-lian Hu; Ya-ying Song; Meng Li (Applied Geophysics, 2025)

Automated modal identification of offshore wind turbines via an uncertainty-quantified stochastic subspace method - Jing Song; Kang Zhou; Zhen-Ru Shu; Xiao-Ying Cai; Ming-Gang Duan (Ocean Engineering, 2025)

Characterization and risk prioritization of PFAS via nontarget screening in soil and maize near a fluoropolymer manufacturing facility - Xiaotong Li; Na Li; Ru-song Zhao; Yali Shi; Yaqi Cai (Journal of Hazardous Materials, 2025)

Recent review on innovative strategies for enhancing the evaporation performance of 3D solar evaporator - Ru Song; Yanlong Shi; Ningshuang Zhang; Peng Wang; Shiyou Li (Journal of Environmental Chemical Engineering, 2025)

Identification of the Q-type ZFP gene family in Triticeaes and drought stress expression analysis in common wheat - Pengyan Guo; Changyan Cui; Baoquan Quan; Jiping Zhao; Jingna Ru; Yanzhen Wang; Zhiyuan Song; Aohui Lin; Shuwen He; Guanghao Wang (Genetica, 2025)

The function of salt responsive promoter of Suaeda salsa SsCLCb explains why the species can accumulate large amount of nitrate from saline soils - Chenyang Li; Runtai Zhao; Ru Liu; Ruiqi Zhang; Xiaolei Yang; Chaoran Shi; Lei Wang; Jie Song (Marine Pollution Bulletin, 2025)

Schwertmannite maintains effective stabilization of arsenic in flooded paddy soil: Insights from a two-season rice experiment and underlying mechanisms - Ru Wang; Yang Song; Yinglin Guo; Nan Ge; Xiaomeng Wang; Lixiang Zhou; Guanyu Zheng (Journal of Hazardous Materials, 2025)

Ionic liquids accelerate the crystallization of a magnetic fluorine-functionalized 3D covalent organic framework for efficient capture of trace benzoylurea insecticides in juices and beverages - Zekun Liu; Lu Liu; Yan Dong; Yan Li; Chong Zhang; Xiao-Li Wang; Lingxi Zhao; Hai-Long Jiang; Yong-Ning Wu; Xiangfeng Chen; Feng Li; Ru-Song Zhao (Chemical Engineering Journal, 2025)

Inspired by traditional printing pastes: Green eco-design of phytic acid-modified starch and durable flame-retardant cellulose-based fabrics - Wan-Meng Song; Bao-Hong Wang; Ru-Yu Fan; Yun Liu; Yu-Zhong Wang (Chemical Engineering Journal, 2025)

Porous Janus membrane for ultrasensitive detection and efficient degradation of sulfur mustard simulant - Meiyang Jin; Shuya Liu; Hailong Jiang; Xia Wang; Yongxian Guo; Yanjun Gong; Qiongzheng Hu; Ru-Song Zhao (Journal of Hazardous Materials, 2025)

Polyphenol-synthesized nanoparticles with ALDH3A1 delivery ability for activating estrogen signaling for diabetic wound healing - Xiaoxuan Ma; Yiqiong Liu; Jingsi Jiang; Yi Ru; Ying Luo; Jiankun Song; Zhan Zhang; Ying Zhang; Dan Yang; Haotian Xu; Haiqing Dong; Yongyong Li; et al. (Chemical Engineering Journal, 2025)

Subsurface organic ameliorant is beneficial in reducing inorganic carbon loss and improving carbon sequestration in saline soils - Ru Yu; Jiashen Song; Jie Zhou; Fangdi Chang; Xiaobin Li; Jing Wang; Haoruo Li; Xia Zhang; Hua Zhang; Yuexin Zhang; Hongyuan Zhang; Yuyi Li (Applied Soil Ecology, 2025)

Green manure roots return drives saline-alkali soil organic carbon accumulation via microbial necromass formation - Fangdi Chang; Hongyuan Zhang; Peiyi Zhao; Na Zhao; Jiashen Song; Ru Yu; Jing Wang; Xiquan Wang; Dongxun Han; Xiaodong Liu; Jie Zhou; Yuyi Li (Soil and Tillage Research, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Arabidopsis HSFA1b functions as a heat sensor inhibiting OST1-mediated stomatal closure through its adenylate-cyclase activity - Yu Zhang; Ru-Feng Song; Xiao-Yu Hu; Hui Zhou; Wei Wang; Junli Zhang; Xin Zhang; Liu-Mei Li; Su-Ting Wang; Yuwei Song; Fuyou Xiang; Jingjing Xing; et al. (Molecular Plant, 2025)

Corrigendum to “Characterization of γ-CD-MOF-stabilized thymol pickering emulsion films with enhanced preservation properties for Basa (Pangasius) fish” [Food Chemistry 476 (2025) 143273] - Yiyi Cheng; Xiaoguo Ying; Xuemei Cai; Yin Chen; Yan Xu; Ru Song; Haiyan Gao (Food Chemistry, 2025)

Integration of human sensory evaluation, intelligent E-tongue/E-nose systems, microbiomics, and metabolomics to comprehensively analyze flavor characteristics and dietary improvement mechanisms of processed Buddha's hand fruit - Zi-Xuan Ding; Yue-Hua Chen; Jia-Nuo Zhang; Wen-Yu Wang; Xin-Ru Zhang; Rui-Bo Sun; Hui Zhang; Ming Xie; Hui-Peng Song (Food Bioscience, 2025)

Facile blending modification and high-voltage activation strategy enabled long-cycle performance of single crystalline nickel-rich cathode materials - Honglei Liu; Yong Wu; Deli Li; Chengzhi Hu; Lei Zou; Tao Xu; Qiang Wang; Weijian Tang; Dongxu Liu; Ranlin Dong; Ru Song; Zeheng Yang; et al. (Chemical Engineering Journal, 2025)

A functional transformation of humic acids in bioelectrochemical anaerobic digestion: From inhibitors to electron shuttles and methane precursors - Zheng-Kai An; Ru Jia; Young-Chae Song; Keug-Tae Kim; Seong-Wook Oa (Chemical Engineering Journal, 2025)

Responses of plant community drought resistance and resilience to warming and nitrogen addition vary with recurrent droughts in a semi-arid grassland - Haidao Wang; Jian Song; Yongge Fan; Jianyang Xia; Lin Jiang; Qingshan Zhang; Heng Li; Jingyi Ru; Jiayin Feng; Lingjie Kong; Jiajun Zhang; Xueli Qiu; et al. (Agriculture, Ecosystems & Environment, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Disentangling climate effects of greenhouse gas emissions and land cover change on future gross primary productivity in the Yellow River basin, China - Xutong Ru; Minghui Qi; Haoming Xia; Longxin Qiao; Hongquan Song (Journal of Environmental Management, 2025)

Physicochemical and rheological properties of konjac glucomannan and its mixed gels with κ-carrageenan: Effect of deacetylation by L-arginine - Ting Zhuo; Jun-ru Qi; Jin-song Liao; Hui-ying Wei; Rong Xiao (Food Chemistry, 2025)

Responses of coastal phytoplankton communities to herbicide exposure: enhanced resistance coupled with reduced resilience - Yunsheng Wang; Ziang Zhao; Xiukai Song; Xiangyang Jiang; Jiuqiang Xiong; Shaoguo Ru; Liqiang Yang (Environmental Research, 2025)

Tracing anthropogenic imprints on polybrominated and polychlorinated dibenzo-p-dioxin/furans in soil: A comprehensive field study in an urban agglomeration of China - Ming-Yang Liu; Hui-Ru Li; Ping-An Peng; Ai-Min Song; Yang Li; Fei-Xiang Xie; Yong-Hong Zhang; Jian-Fang Hu (Environmental Research, 2025)

Integrative transcriptome and metabolome analyses provide insights into rice defence against Chilo suppressalis oviposition - Chen Shen; Haibo Bao; Zhengping Yu; Xiaoyan Cang; Ru Zhang; Junxian Song; Guanghua Luo; Jichao Fang (Plant Molecular Biology, 2025)

Combined genome and transcriptome provides insight into the genetic evolution of an edible halophyte Suaeda salsa adaptation to high salinity - Bing Cui; Ranran Liu; Qiong Yu; Jianrong Guo; Xihua Du; Zixin Chen; Chenyang Li; Tong Wang; Ru Liu; Rui He; Congcong Song; Yue Liu; et al. (Molecular Ecology, 2025)
Suaeda salsa L. is a typical halophyte with high value as a vegetable. Here, we report a 447.98 Mb, chromosomal‐level genome of S. salsa , assembled into nine pseudomolecules (contig N50 = 1.36 Mb) and annotated with 27,927 annotated protein‐coding genes. Most of the assembled S. salsa genome, 58.03%, consists of transposable elements. Some gene families including HKT1 , NHX , SOS and CASP related to salt resistance were significantly amplified. We also observed expansion of genes encoding protein that bind the trace elements Zn, Fe, Cu and Mn, and genes related to flavonoid and α‐linolenic acid metabolism. Many expanded genes were significantly up‐regulated under salinity, which might have contributed to the acquisition of salt tolerance in S. salsa . Transcriptomic data showed that high salinity markedly up‐regulated salt‐resistance related genes, compared to low salinity. Abundant metabolic pathways of secondary metabolites including flavonoid, unsaturated fatty acids and selenocompound were enriched, which indicates that the species is a nutrient‐rich vegetable. Particularly worth mentioning is that there was no significant difference in the numbers of cis ‐elements in the promoters of salt‐related and randomly selected genes in S. salsa when compared with Arabidopsis thaliana , which may affirm that plant salt tolerance is a quantitative rather than a qualitative trait in terms of promoter evolution. Our findings provide deep insight into the adaptation of halophytes to salinity from a genetic evolution perspective.

Schiff base crosslinking based dialdehyde-chitosan/gelatin/tea polyphenol electrospun nanofibrous membranes with excellent antibacterial and antioxidant activity for food packaging - Yu Ma; Ru Tian; Yudong Song; Mengxiao Liu; Jie Li; Zhichun Bi; Hui Huang; Yongxin Li (Food Packaging and Shelf Life, 2025)

N,O-interlocked cavity-structured functionalized metal–organic frameworks for one-step efficient removal of highly toxic thorium from tailings wastewater - An-Min Song; Zhi Wu; Bin Lin; Meng-Jie Yang; Qing Yang; Shu-Yuan Zhang; Xiao-Xing Wang; Zhi-Hai Peng; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2025)

Safranal ameliorates atherosclerosis progression partly via repressing PI3K/Akt and NF-κB signaling pathways in ApoE (−/−) mice - Yining Geng; Manping Song; Bing Huang; Ru Lin; Shiwen Wu; An Lin (Journal of Natural Medicines, 2025)

Climate change, social environment, health, and urban inequality: Developing a novel adaptive evaluation framework - Nan Jia; Yinshuai Li; Zhimeng Jiang; Rongfei Su; Xin Lan; Kai Zhang; Wen Song; Rui Zhao; Zilong Xia; Yongze Song; Zehua Zhang; Mengting Wang; et al. (Sustainable Cities and Society, 2025)

Structural evaluation and formation regularities of garlic clove-like meat in prefabricated grass carp - Qin Yang; Junhong Xie; Yuting Zhang; Yiling Tian; Liang Song; Yongqiang Zhao; Jian Xiong; Ru Liu; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Chemistry, 2025)

Characterization of γ-CD-MOF-stabilized thymol Pickering emulsion films with enhanced preservation properties for Basa (Pangasius) fish - Yiyi Cheng; Xiaoguo Ying; Xuemei Cai; Yin Chen; Yan Xu; Ru Song; Haiyan Gao (Food Chemistry, 2025)

Superior ammonia nitrogen adsorption capacity and reusability biochar microsphere applied in live fish transportation - Ling Peng; Tao Yin; Zhiyong Song; Shanbai Xiong; Ru Liu; Juan You; Qiling Huang (Chemical Engineering Journal, 2025)

Citrus endogenous components as prebiotics: Advances in extraction, digestion, mechanisms, and delivery - Wei-yun Zhang; Jin-song Liao; Jun-ru Qi (Food Research International, 2025)

Electrospun nanofiber membranes based on dialdehyde pullulan polysaccharide and schiff base crosslinked lysozyme for antibacterial packaging of blueberries - Yu Ma; Ru Tian; Yudong Song; Chenghui Yin; Hui Huang; Yongxin Li (Food Bioscience, 2025)

Synthesis of hollow HC-Ni0.96S@MXene/C nanobox as advanced anode for lithium-ion and sodium-ion battery - Song-Yi Liao; Jing Chen; Dao-Ren Deng; Cai-Yun Wu; Selina X. Yao; Yi Wang; Yu-Ming Ru; Xiao-Yan Li; Xu-Gang Shu; Yong-Gang Min (Chemical Engineering Journal, 2025)

Generation characteristics of polybrominated and polychlorinated dibenzo-p-dioxins/furans (PBDD/Fs and PCDD/Fs) under varying incineration conditions of municipal solid waste - Ming-Yang Liu; Ai-Min Song; Hui-Ru Li; Sheng-Tao Ma; Ren-Jie Shang; Yao Xiao; Ping-An Peng; Jian-Fang Hu (Environmental Pollution, 2025)

Efficient fluconazole degradation by activating peroxymonosulfate with LDH-coated nickel foam: Synergism of radical and non-radical pathways - Xiang-Yang Li; Ling-Xi Zhao; Meng Xie; Ning Liu; Xiang-Feng Chen; Ru-Song Zhao (Journal of Water Process Engineering, 2025)

Efficient adsorption behavior of Fe-based ternary magnetic LDHs for naphthalene acetic acid: Role of Fe element - Ning Liu; Ti-Bo Fang; Ling-Xi Zhao; Na Li; Xiang-Feng Chen; Ru-Song Zhao (Environmental Research, 2025)

Modulation of gut microbiota by pectin: The critical role of degree of esterification and rhamnogalacturonan-I ratios - Wei-yun Zhang; Jin-song Liao; Jun-ru Qi (Food Bioscience, 2025)

Co-influence of the degree of esterification and degree of amidation on the properties of acid-sugar-calcium amidated pectin gels - Hui-ying Wei; Jun-ru Qi; Jin-song Liao; Ting Zhuo; Rong Xiao (Food Hydrocolloids, 2025)

One-step open-ring strategy for constructing sandwich-like metal–organic framework with highly selective removal of thorium - Meng-Jie Yang; An-Min Song; Qing Yang; Zhi Wu; Bin Lin; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2025)

The Interplay Between Accumulation of Amyloid-Beta and Tau Proteins, PANoptosis, and Inflammation in Alzheimer’s Disease - Xianbo Zhuang; Jie Lin; Yamin Song; Ru Ban; Xin Zhao; Zhangyong Xia; Zheng Wang; Guifeng Zhang (NeuroMolecular Medicine, 2024)

Bacterial necromass as the main source of organic matter in saline soils - Jiashen Song; Hongyuan Zhang; Bahar Razavi; Fangdi Chang; Ru Yu; Xia Zhang; Jing Wang; Jie Zhou; Yuyi Li; Yakov Kuzyakov (Journal of Environmental Management, 2024)

Advanced growing-season precipitation peak promotes soil nitrogen mineralization in a semi-arid grassland - Jiayin Feng; Xiaojing Yue; Benqing Li; Jingyi Ru; Zhenxing Zhou; Lingjie Kong; Jiajun Zhang; Jiaxin Zhou; Guilin Zhou; Wenjing Ma; Yaru Lyu; Jian Song; et al. (CATENA, 2024)

PRDX1 Interfering Peptide Disrupts Amino Acids 70–90 of PRDX1 to Inhibit the TLR4/NF-κB Signaling Pathway and Attenuate Neuroinflammation and Ischemic Brain Injury - Xiang-Yu Ma; Cheng-yu Qi; Xing-yi Xu; Hui Li; Chang-Dong Liu; Xiang-Ru Wen; Yan-Yan Fu; Yan Liu; Jia Liang; Cheng-Yu Huang; Dan-Dan Li; Yan Li; et al. (Molecular Neurobiology, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Electrospun film polyvinyl alcohol/chitosan loaded with cinnamon essential oil and inhibitory effects on polyphenol oxidase and dominant spoilage bacteria from Pacific white shrimp - Minzhen Zhang; Lin Wang; Xiaoyu Zou; Ru Song (Food Hydrocolloids, 2024)

Tuning local charge polarization of covalent organic frameworks for enhanced photocatalytic uranium (VI) reduction - Xiao-Xing Wang; Cheng-Rong Zhang; Rui-Xiang Bi; Zhi-Hai Peng; Hao-Xuan He; Rui Zhang; An-Min Song; Jia-Xin Qi; Xiao-Juan Chen; Xin Liu; Yuan-Jun Cai; Ru-Ping Liang; et al. (Chemical Engineering Journal, 2024)

Changes in plant litter and root carbon inputs alter soil respiration in three different forests of a climate transitional region - Jiayin Feng; Chunyu Wang; Jingjing Gao; Huixia Ma; Zheng Li; Yuanfeng Hao; Xueli Qiu; Jingyi Ru; Jian Song; Shiqiang Wan (Agricultural and Forest Meteorology, 2024)

Ingenane-type diterpenoids inhibit non-small cell lung cancer cells by regulating SRC/PI3K/Akt pathway - Xin-Ye Wang; Yu-Jue Wang; Zi-Lin Hou; Bo-Wen Guo; Ru-Qi Wang; Qingbo Liu; Guo-Dong Yao; Shao-Jiang Song (Natural Product Research, 2024)

Magnetic conjugated microporous polymer for rapid extraction and sensitive analysis of environmental endocrine disruptors in environmental waters and dairy products - Hai-Long Jiang; Fu-Shuai Kang; Ye-Fei Fan; Xia Wang; Yun-Liang Lin; Lu Liu; Wei Liu; Yan-Fang Zhao; Ru-Song Zhao (Analytica Chimica Acta, 2024)

Applications in Pickering emulsions of enhancing preservation properties: Current trends and future prospects in active food packaging coatings and films - Yiyi Cheng; Xuemei Cai; Xin Zhang; Yadong Zhao; Ru Song; Yan Xu; Haiyan Gao (Trends in Food Science & Technology, 2024)

Pollution level and ecological risk assessment of triazine herbicides in Laizhou Bay and derivation of seawater quality criteria - Zhenzhong Zhang; Yongliang Feng; Weizhong Wang; Shaoguo Ru; Lingchao Zhao; Yuanqing Ma; Xiukai Song; Lijuan Liu; Jun Wang (Journal of Hazardous Materials, 2024)

The effectiveness of gliding arc discharge plasma in sterilizing artificial seawater contaminated with Vibrio parahaemolyticus - Meng-Ru Du; Yu-yi Guo; Han-ze Wei; Yu-pan Zhu; Rong-rong Liu; Ruo-nan Ma; Fu-kun Shi; Jin-song Guo; Jie Zhuang (Journal of Hazardous Materials, 2024)

Enhancing vitamin D3 bioaccessibility: Unveiling hydrophobic interactions in soybean protein isolate and vitamin D3 binding via an infant in vitro digestion model - Jia-Rong Huang; Jing-Ru Song; Wan-Shuang Cai; Zhen-Wen Shao; Da-Yong Zhou; Liang Song (Food Chemistry, 2024)

Thiophene-containing conjugated polymers modified Zn0.5Cd0.5S inorganic/organic S-scheme heterojunction for boosting photocatalytic hydrogen production coupled with benzyl alcohol oxidation - Lele Wei; Ru Song; Jiarui Song; Yaping Li; Yina Nie; Lin Liu; Jun Wan (Chemical Engineering Journal, 2024)

Alginate/silk fibroin/Zn2+ composite microspheres for site-specific delivery for enhanced ulcerative colitis therapy - Yaoyao Du; Yuting Jiang; Yijie Song; Jie Chen; Yueqian Wu; Ru Guo; Yihao He; Lan Shen; Bing Wang; Shaogang Huang; Yongzhuo Huang (Chemical Engineering Journal, 2024)

Additive effects of N addition and changing precipitation on soil respiration in a climate transitional forest - Jiayin Feng; Jingjing Gao; Huixia Ma; Chunyu Wang; Yuanfeng Hao; Zheng Li; Jingru Zou; Xueli Qiu; Jingyi Ru; Jian Song; Shiqiang Wan (CATENA, 2024)

Antioxidant properties and L-asparaginase activities of endophytic fungi from Cymbidium orchids - Ru Wei Chua; Keang Peng Song; Adeline Su Yien Ting (Folia Microbiologica, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Hydroxyl-containing triazine-based conjugated microporous polymers for solid phase extraction of fluoroquinolone antibiotics in the environment and food samples - Lu-Shu Meng; Xiao-Li Wang; Xia Wang; Lei Ji; Lei-Lei Wang; Ya-Qi Cai; Ru-Song Zhao (Food Chemistry, 2024)

Efficient activation of peracetic acid by cobalt modified nitrogen-doped carbon nanotubes for drugs degradation: Performance and mechanism insight - Mingya Yao; Shuofeng Zhang; Meng Xie; Lingxi Zhao; Ru-Song Zhao (Chemosphere, 2024)

Zinc isotope evidence for enhanced organic carbon burial driving transient oxygenation of the Mesoproterozoic ocean - Kexin Song; Dandan Li; Yi-Wen Lv; Chengshuai Yuan; Yuan-Ru Qu; Sheng-Ao Liu (Precambrian Research, 2024)

Inorganic carbon accumulation in saline soils via modification effects of organic amendments on dissolved ions and enzymes activities - Jiashen Song; Hongyuan Zhang; Kazem Zamanian; Fangdi Chang; Ru Yu; Jing Wang; Jie Zhou; Yuyi Li (CATENA, 2024)

Cadmium Treatment Affected the Growth and Physiology of Larix Olgensis Seedlings, the Chemical Properties of Haplic Cambisols and Toxicity Threshold Determination - Haixia Wang; Kunshu Yao; Jiaxin Ru; Jiagui Guo; Ding Liu; Yunlong Liu; LingYun Bai; Jixiang Lin; Chengbo Gu; Jinfeng Song (Journal of Soil Science and Plant Nutrition, 2024)

Candidate gene mining of GA-mediated regulation of pear fruit shape - Zeyu Xue; Ru Yang; Yadong Wang; Yuchen Ma; Yujing Lin; Zhengao Li; Yuqin Song; Xinxin Feng; Liulin Li (Horticulture, Environment, and Biotechnology, 2024)

Multi-omics analysis reveals mechanism of Schisandra chinensis lignans and acteoside on EMT in hepatoma cells via ERK1/2 pathway - Jingjing Jiang; Ru Cheng; Aoqi Song; Yuefen Lou; Guorong Fan (Functional & Integrative Genomics, 2024)

One-step bioremediation of hypersaline and nutrient-rich food industry process water with a domestic microbial community containing diatom Halamphora coffeaeformis - Song Wang; Chenzhi Zhang; Kai Zhang; Ling Zhang; Ru Bi; Yuxin Zhang; Zhangli Hu (Water Research, 2024)

Effects of land use and land cover change under shared socioeconomic pathways on future climate in the Yellow River basin, China - Xutong Ru; Longxin Qiao; Haopeng Zhang; Tianqi Bai; Ruiqi Min; Yaobin Wang; Qianfeng Wang; Hongquan Song (Urban Climate, 2024)

BDNF mimetics recover palmitic acid-induced injury in cardiomyocytes by ameliorating Akt-dependent mitochondrial impairments - Man-Ru Zhang; Bang-Yun Zuo; Yu-Chen Song; Dan-Dan Guo; Qing-Liu Li; Jin-Xiu Lyu; Hua Zhu; Jing Zhao; Peng-Zhou Hang (Toxicology and Applied Pharmacology, 2024)

Green manure removal with reduced nitrogen improves saline-alkali soil organic carbon storage in a wheat-green manure cropping system - Fangdi Chang; Hongyuan Zhang; Na Zhao; Peiyi Zhao; Jiashen Song; Ru Yu; Zhengrong Kan; Xiquan Wang; Jing Wang; Hanjiang Liu; Dongxun Han; Xinya Wen; et al. (Science of The Total Environment, 2024)

Nighttime warming and nitrogen addition effects on the microclimate of a freshwater wetland dominated by Phragmites australis - Yunpeng Guo; Jian Song; Jiayin Feng; Hongpeng Wang; Jinhua Zhang; Jingyi Ru; Xiaopan Wang; Xu Han; Huixia Ma; Yaru Lyu; Wenjing Ma; Chao Wang; et al. (Science of The Total Environment, 2024)

Effect of ultrasound-assisted enzyme pretreatment on γ-aminobutyric acid content, eating quality and starch properties of germinated brown rice - Bing-jie Chen; Xiao Wang; Hong-ru Liu; Yi Zhang; Song-heng Wu; Chun-fang Wang; Chen-xia Liu; Yong-jin Qiao (Journal of Cereal Science, 2024)

High-Performance enrichment and sensitive analysis of bisphenol and its analogues in water and milk using a novel Ni-Based cationic Metal-Organic framework - Jin-Yan Ma; Hai-Long Jiang; Fu-Shuai Kang; Lu Liu; Xia Wang; Ru-Song Zhao (Food Chemistry, 2024)

Development, characteristics and biological activities of bilayer composite film based on gelatin/κ-carrageenan loading curcumin and ε-polylysine - Xihan Yang; Minzhen Zhang; Baoding Zhao; Xiaoyu Zou; Ru Song (Food Hydrocolloids, 2024)

A novel ionic-liquid-mediated covalent organic framework as a strong electrophile for high-performance iodine removal - Jie Fu; Jia-Ying Liu; Yue-Ru Zhou; Lei Zhang; Shuang-Long Wang; Song Qin; Maohong Fan; Guo-Hong Tao; Ling He (Chemical Engineering Journal, 2024)

Differentiation of closely-related species within Acinetobacter baumannii-calcoaceticus complex via Raman spectroscopy: a comparative machine learning analysis - Xue-Song Xiong; Lin-Fei Yao; Yan-Fei Luo; Quan Yuan; Yu-Ting Si; Jie Chen; Xin-Ru Wen; Jia-Wei Tang; Su-Ling Liu; Liang Wang (World Journal of Microbiology and Biotechnology, 2024)

Hyperphosphorylated Tau Inflicts Intracellular Stress Responses that Are Mitigated by Apomorphine - Zhenfeng Song; Kuang-Wei Wang; Hsiao-Tien Chien Hagar; Hong-Ru Chen; Chia-Yi Kuan; Kezhong Zhang; Min-Hao Kuo (Molecular Neurobiology, 2024)
Abnormal phosphorylation of the microtubule-binding protein tau in the brain is a key pathological marker for Alzheimer’s disease and additional neurodegenerative tauopathies. However, how hyperphosphorylated tau causes cellular dysfunction or death that underlies neurodegeneration remains an unsolved question critical for the understanding of disease mechanism and the design of efficacious drugs. Using a recombinant hyperphosphorylated tau protein (p-tau) synthesized by the PIMAX approach, we examined how cells responded to the cytotoxic tau and explored means to enhance cellular resistance to tau attack. Upon p-tau uptake, the intracellular calcium levels rose promptly. Gene expression analyses revealed that p-tau potently triggered endoplasmic reticulum (ER) stress, unfolded protein response (UPR), ER stress-associated apoptosis, and pro-inflammation in cells. Proteomics studies showed that p-tau diminished heme oxygenase-1 (HO-1), an ER stress-associated anti-inflammation and anti-oxidative stress regulator, while stimulated the accumulation of MIOS and other proteins. p-Tau-induced ER stress-associated apoptosis and pro-inflammation are ameliorated by apomorphine, a brain-permeable prescription drug widely used to treat Parkinson’s disease symptoms, and by overexpression of HO-1. Our results reveal probable cellular functions targeted by hyperphosphorylated tau. Some of these dysfunctions and stress responses have been linked to neurodegeneration in Alzheimer’s disease. The observations that the ill effects of p-tau can be mitigated by a small compound and by overexpressing HO-1 that is otherwise diminished in the treated cells inform new directions of Alzheimer’s disease drug discovery.

Nitrogen addition does not alter symmetric responses of soil respiration to changing precipitation in a semi-arid grassland - Lingjie Kong; Jian Song; Jingyi Ru; Jiayin Feng; Jiawei Hou; Xueke Wang; Qingshan Zhang; Haidao Wang; Xiaojing Yue; Zhenxing Zhou; Dasheng Sun; Jiajia Zhang; et al. (Science of The Total Environment, 2024)

Cultivating edible bio-inks: Elevating 3D printing with medium-internal-phase emulsion gel incorporating soybean protein isolate microgel particles - Jing-ru Song; Jia-rong Huang; Si-xu Ren; Hong-ze Zheng; Da-yong Zhou; Liang Song (Food Hydrocolloids, 2024)

On the origin of selectivity in extracting and separating lanthanide ions by alkyl-nitrilotriacetamide - Yu-Chang Hou; Juan Wang; Yuan-Ru Guo; Song-Dong Ding; Qing-Jiang Pan (Chemical Engineering Journal, 2024)

Subsurface organic amendment of a saline soil increases ecosystem multifunctionality and sunflower yield - Jiashen Song; Hongyuan Zhang; Fangdi Chang; Ru Yu; Jing Wang; Aiping Chen; Yang Xu; Yu Liu; Jie Zhou; Yuyi Li (Science of The Total Environment, 2024)

Facile synthesis of hydroxylated triazine-based magnetic microporous organic network for ultrahigh adsorption of phenylurea herbicides: An experimental and density-functional theory study - Lu Liu; Lu-Qin Qiao; Feng Liu; Qian-Yun Sun; Yan-Fang Zhao; Xiao-Li Wang; Na Li; Hai-Long Jiang; Xiang-Feng Chen; Ming-Lin Wang; Yong-Ning Wu; Ru-Song Zhao (Journal of Hazardous Materials, 2024)

Influence on the volatilization of ethyl esters: Nonnegligible role of long-chain fatty acids on Baijiu flavor via intermolecular interaction - Qing-Ru Liu; Xian-Li Lin; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Xiao-Juan Zhang; Zheng-Hong Xu (Food Chemistry, 2024)

Efficient synthesis of squalene by cytoplasmic-peroxisomal engineering and regulating lipid metabolism in Yarrowia lipolytica - Yang Ning; Mengsu Liu; Ziyun Ru; Weizhu Zeng; Song Liu; Jingwen Zhou (Bioresource Technology, 2024)

Design of a tulobuterol patch with improved mechanical properties: effect of transdermal permeation enhancers on the release process of metal ligand-based acrylic pressure-sensitive adhesives - Longyi Nan; Haoyuan Song; Haijun Wang; Ru Mi; Xiaoxu Wang; Liang Fang (Drug Delivery and Translational Research, 2024)

Efficient electro-demulsification of O/W emulsions and simultaneous oil removal enabled by a multiscale porous biocarbon electrode - Kui Wang; Hailiang Zhao; Yingming Zhang; Xu Li; Mengyi Xu; Meirong Song; Guangxin Ru; Xiaolei Jiang; Xiuhong Zhu; Dandan Han; Yutao Dong; Kexin Shen; et al. (Chemical Engineering Journal, 2024)

Low-temperature fabrication of potassium single-atom solid base catalysts with high activity in transesterification - Xiang-Bin Shao; Xing-Ru Song; Song-Song Peng; Xiao-Qin Zheng; Shi-Chao Qi; Peng Tan; Xiao-Qin Liu; Lin-Bing Sun (Chemical Engineering Journal, 2024)

Mixed sowing of Feed rape and Vicia villosa can substitute nitrogen fertilizer to improve soil multifunctionality in the Hetao irrigation District - Ru Yu; Hongyuan Zhang; Fangdi Chang; Jiashen Song; Jing Wang; Xiquan Wang; Zhengrong Kan; Na Zhao; Xiaohong Li; Jun Ma; Yuyi Li (CATENA, 2024)

Mechanism of enhanced microalgal biomass and lipid accumulation through symbiosis between a highly succinic acid-producing strain of Escherichia coli SUC and Aurantiochytrium sp. SW1 - Mei-Yu Zhang; Xin-Ru Xu; Ru-Ping Zhao; Chao Huang; Yuan-Da Song; Zi-Tong Zhao; Yu-Bin Zhao; Xiao-Jie Ren; Xin-He Zhao (Bioresource Technology, 2024)

Phycoremediation and valorization of hypersaline pickled mustard wastewater via Chaetoceros muelleri and indigenous bacteria - Kai Zhang; Shuqin Jiang; Juan Zhang; Jishu Zheng; Ping Li; Song Wang; Ru Bi; Lihong Gao (Bioresource Technology, 2024)

ABA functions in low phosphate-induced anthocyanin accumulation through the transcription factor ABI5 in Arabidopsis - Ru-Feng Song; Xiao-Yu Hu; Wen-Cheng Liu; Hong-Mei Yuan (Plant Cell Reports, 2024)

TAT-W61 peptide attenuates neuronal injury through blocking the binding of S100b to the V-domain of Rage during ischemic stroke - Jia Liang; Hui Li; Chang‑Dong Liu; Xiao‑Yan Zhou; Yan‑Yan Fu; Xiang-Yu Ma; Dan Liu; Yu-Ling Chen; Qian Feng; Zhen Zhang; Xiang-Ru Wen; Guang Zhu; et al. (Journal of Molecular Medicine, 2024)

Intravenous immunoglobulin for treatment of hospitalized COVID-19 patients: an evidence mapping and meta-analysis - Mei-xuan Li; Yan-fei Li; Xin Xing; Jun-qiang Niu; Liang Yao; Meng-ying Lu; Ke Guo; Mi-na Ma; Xiao-tian Wu; Ning Ma; Dan Li; Zi-jun Li; et al. (Inflammopharmacology, 2024)

An Ensemble CNOP Method Based on a Pre-Screening Mechanism for Targeted Observations in the South China Sea - Ru Wang; Qingyu Zheng; Wei Li; Guijun Han; Xuan Wang; Song Hu (Journal of Marine Science and Engineering, 2024)
The uncertainty in the initial condition seriously affects the forecasting skill of numerical models. Targeted observations play an important role in reducing uncertainty in numerical prediction. The conditional nonlinear optimal perturbation (CNOP) method is a useful tool for studying adaptive observation. However, the traditional CNOP method highly relies on the adjoint model, and it is difficult to find the global optimal solution. In this paper, a pre-screening and ensemble CNOP hybrid method called PECNOP is proposed to identify optimal sensitive areas in targeted observations. PECNOP is an adjoint-free method that captures global CNOP with high probability, which can effectively solve the two major problems faced by traditional CNOP methods. We evaluated the performance of PECNOP by building an observation simulation system consisting of an ocean model and data assimilation. One of the assimilation experiments was dedicated to evaluating the stability and effectiveness of PECNOP in extreme events. The results show that, compared with traditional methods, PECNOP can stably capture the global CNOP. Extra observations and assimilation in the optimal sensitive areas identified by PECNOP can effectively improve forecasting by about 20% within 30 days. Therefore, PECNOP has potential to reduce the initial error of numerical models, which is important for improving forecasting.

Soil microbial diversity and network complexity drive the ecosystem multifunctionality of temperate grasslands under changing precipitation - Changchun Zhai; Lili Han; Chao Xiong; Anhui Ge; Xiaojing Yue; Ying Li; Zhenxing Zhou; Jiayin Feng; Jingyi Ru; Jian Song; Lin Jiang; Yunfeng Yang; et al. (Science of The Total Environment, 2024)

Study on low methoxyl pectin (LMP) with varied molecular structures cross-linked with calcium inducing differences in the gel properties - Chun-lin Wu; Jun-ru Qi; Jin-song Liao; Zi-wei Liu; Chun-ai He (Food Hydrocolloids, 2024)

High-strength ionic hydrogel constructed by metal-free physical crosslinking strategy for enhanced uranium extraction from seawater - Yuan-Hao Wang; Yu-Qin Xiang; Qian Huang; Xiao-Lan Yang; Shuang-Long Wang; Yue-Ru Zhou; Song Qin; Ling-Qiong Gou; Guo-Hong Tao; Ling He (Chemical Engineering Journal, 2024)

Burying straw interlayers decreases CO2 emissions in deep saline soil - Jiashen Song; Hongyuan Zhang; Leanne Peixoto; Fangdi Chang; Ru Yu; Xiquan Wang; Jing Wang; Jufeng Cao; Jie Zhou; Amit Kumar; Yuyi Li (Sustainable Production and Consumption, 2023)

Investigation on molecular characteristics of organic compounds during a full-scale landfill leachate treatment process based on non-targeted analysis - Ninghui Song; Qian Zhang; Yixuan Wang; Li Gao; Sitao Liu; Hao Yao; Ru Liu; Hang Xu (Environmental Research, 2023)

Predicting energy consumption of chiller plant using WOA-BiLSTM hybrid prediction model: A case study for a hospital building - Yang Song; Hui Xie; Zhengwei Zhu; Ru Ji (Energy and Buildings, 2023)

Topology optimization on periodic pile barriers considering material damping based on complex band diagrams - Peng Zhou; Shui Wan; Xiao Wang; Aiming Song; Ru Yue (Computers and Geotechnics, 2023)

Humic acid plus manure increases the soil carbon pool by inhibiting salinity and alleviating the microbial resource limitation in saline soils - Jiashen Song; Hongyuan Zhang; Fangdi Chang; Ru Yu; Xiangqian Zhang; Xiquan Wang; Weini Wang; Junmei Liu; Jie Zhou; Yuyi Li (CATENA, 2023)

Characterization and antimicrobial activities of bioactive compounds from endophytic Trichoderma asperellum isolated from Dendrobium orchids - Ru Wei Chua; Keang Peng Song; Adeline Su Yien Ting (Biologia, 2023)

Recent advances in the unlined cast iron pipe scale characteristics, cleaning techniques and harmless disposal methods: An overview - Ming Li; Dong Zhang; Ru Zhang; Fang Wang; Yang Song; Feiyong Chen; Juan Yang; Changming Li (Chemosphere, 2023)

Excellent hydration properties and oil holding capacity of citrus fiber: Effects of component variation and microstructure - Chun-ai He; Jun-ru Qi; Jin-song Liao; Ya-ting Song; Chun-lin Wu (Food Hydrocolloids, 2023)

Organophosphate esters (OPEs) in a heavily polluted river in South China: Occurrence, spatiotemporal trends, sources, and phase distribution - Yi-Shan Liu; Hui-Ru Li; Zhi-Lang Lao; Sheng-Tao Ma; Zi-Cong Liao; Ai-Min Song; Ming-Yang Liu; You-Sheng Liu; Guang-Guo Ying (Environmental Pollution, 2023)

Cyclodextrin-based metal-organic framework materials: Classifications, synthesis strategies and applications in variegated delivery systems - Ru-nan Zhao; Bei-wei Zhu; Yu Xu; Song-feng Yu; Wen-jun Wang; Dong-hong Liu; Jiang-ning Hu (Carbohydrate Polymers, 2023)

Multivariate Sea Surface Prediction in the Bohai Sea Using a Data-Driven Model - Song Hu; Qi Shao; Wei Li; Guijun Han; Qingyu Zheng; Ru Wang; Hanyu Liu (Journal of Marine Science and Engineering, 2023)
Data-driven predictions of marine environmental variables are typically focused on single variables. However, in real marine environments, there are correlations among different oceanic variables. Additionally, sea–air interactions play a significant role in influencing the evolution of the marine environment. Both internal dynamics and external drivers contribute to these changes. In this study, a data-driven model is proposed using sea surface height anomaly (SSHA), sea surface temperature (SST), and sea surface wind (SSW) in the Bohai Sea. This model combines multivariate empirical orthogonal functions (MEOFs) with long and short-term memory (LSTM). MEOF analysis is used on the multivariate dataset of SSHA and SST, considering the correlation among sea surface variables. SSW is introduced as a predictor to enhance the predictability of the multivariate sea surface model. In the case of the Bohai Sea, the comparative tests of the model without wind field effect, the fully coupled model, and the proposed prediction model were carried out. MEOF analysis is employed in comparative experiments for oceanic variables, atmospheric variables, and combined atmospheric and oceanic variables. The results demonstrate that using wind field as a predictor can improve the forecast accuracy of SSHA and SST in the Bohai Sea. The root mean square errors (RMSE) for SSHA and SST in a 7-day forecast are 0.016 m and 0.3200 °C, respectively.

Feasibility of Wave Simulation in Typhoon Using WAVEWATCH-III Forced by Remote-Sensed Wind - Ru Yao; Weizeng Shao; Youguang Zhang; Meng Wei; Song Hu; Juncheng Zuo (Journal of Marine Science and Engineering, 2023)
The purpose of our work was to assess the feasibility of hindcasting waves using WAVEWATCH-III (WW3) in a typhoon by assembling winds from multiple remote-sensed products. During the typhoon season in 2021–2022, the swath wind products in the Western Pacific Ocean were collected from scatterometers and radiometers. Cyclonic winds with a spatial resolution of 0.125° at intervals of 6 h were obtained by assembling the remote-sensed winds from those satellites. The maximum wind speeds, Vmax, were verified using the reanalysis data from the National Hurricane Center (NHC), yielding a root-mean-squared error (RMSE) of 4.79 m/s and a scatter index (SI) value of 0.2. The simulated wave spectrum was compared with the measurements from Surface Waves Investigation and Monitoring (SWIM) carried out on the Chinese–French Oceanography Satellite (CFOSAT), yielding a correlation coefficient (Cor) of 0.80, squared error (Err) of 0.49, RMSE of significant wave height (SWH) of 0.48 m with an SI of 0.25, and an RMSE of the peak wave period (PWP) of 0.95 s with an SI of 0.10. The bias of wave (WW3 minus European Centre for Medium-Range Weather Forecasts (ECMWFs) reanalysis (ERA-5)) concerning the bias of wind (assembling minus ERA-5) showed that the WW3-simulated SWH with the assembling wind forcing was significantly higher than that with the ERA-5 wind forcing. Moreover, the bias of SWH gradually increased with an increasing bias of wind speed; i.e., the bias of SWH increased up to 4 m as the bias of wind speed reached 30 m/s. It was concluded that the assembling wind from multiple scatterometers and radiometers is a promising source for wave simulations via WW3 in typhoons.

Boron nitride quantum dots-enhanced laser desorption/ionization mass spectrometry analysis and imaging of bisphenol A - Yanfang Zhao; Rabah Boukherroub; Lu Liu; Huizhi Li; Ru-Song Zhao; Qin Wei; Xiang Yu; Xiangfeng Chen (Journal of Hazardous Materials, 2023)

Ozone exposure associates with sperm quality indicators: Sperm telomere length as a potential mediating factor - Zhong-Hua Lu; Bin Sun; Yi-Xin Wang; Ya-Ru Wu; Yu-Jie Chen; Sheng-Zhi Sun; Shi-Jia Liang; Song Xu; Hao Chang; Heng-Gui Chen; Jie Zhang (Journal of Hazardous Materials, 2023)

Once-middle amount of straw interlayer enhances saline soil quality and sunflower yield in semi-arid regions of China: Evidence from a four-year experiment - Fangdi Chang; Hongyuan Zhang; Jiashen Song; Ru Yu; Xia Zhang; Haoruo Li; Jing Wang; Zhengrong Kan; Yuyi Li (Journal of Environmental Management, 2023)

Comparative analysis of antimicrobial compounds from endophytic Buergenerula spartinae from orchid - Ru Wei Chua; Keang Peng Song; Adeline Su Yien Ting (Antonie van Leeuwenhoek, 2023)

Effects of photochlorination on the physicochemical transformation of polystyrene nanoplastics: Mechanism and environmental fate - Tingting Du; Song Shao; Liwen Qian; Ru Meng; Tong Li; Lijun Wu; Yao Li (Water Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

A bibliometric review on electric vehicle (EV) energy efficiency and emission effect research - Shengyong Yao; Zixiang Bian; Mohammad Kamrul Hasan; Ru Ding; Shuning Li; Yanfei Wang; Shulei Song (Environmental Science and Pollution Research, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Au@BN-enhanced laser desorption/ionization mass spectrometry and imaging for determination of fipronil and its metabolites in food and biological samples - Yanfang Zhao; Rabah Boukherroub; Guiju Xu; Huijuan Li; Ru-Song Zhao; Qin Wei; Xiang Yu; Xiangfeng Chen (Food Chemistry, 2023)

Potential application of lactic acid bacteria for controlling discoloration in tuna (Thunnus orientalis) - Du-Min Jo; Mi-Ru Song; Seul-Ki Park; Ji-Hwan Choi; Do Kyung Oh; Deok Hoon Kim; Young-Mog Kim (Food Bioscience, 2023)

First transcriptome profiling in gill and hepatopancrease tissues of Metapenaeus ensis in response to acute ammonia-N stress - Yun-Dong Li; Meng-Ru Si; Shi-Gui Jiang; Qi-Bin Yang; Song Jiang; Li-Shi Yang; Jian-Hua Huang; Fa-Lin Zhou (Fish & Shellfish Immunology, 2023)

A Co2N/CoP p-n junction with modulated interfacial charge and rich nitrogen vacancy for High-Efficiency water splitting - Chunfang Guo; Hui Xue; Jing Sun; Niankun Guo; Tianshan Song; Jiawen Sun; Yi-Ru Hao; Qin Wang (Chemical Engineering Journal, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

Xanthine-derived reactive oxygen species exacerbates adipose tissue disorders in male db/db mice induced by real-ambient PM2.5 exposure - Leijian Chen; Huankai Li; Yi Ru; Yuanyuan Song; Yuting Shen; Lifang Zhao; Gefei Huang; Yi Chen; Zenghua Qi; Ruijin Li; Chuan Dong; Jiacheng Fang; et al. (Science of The Total Environment, 2023)

Nonagricultural emissions enhance dimethylamine and modulate urban atmospheric nucleation - Yunhua Chang; Qingyang Ling; Xinlei Ge; Xiangyang Yuan; Shengqian Zhou; Kai Cheng; Jianjiong Mao; Dandan Huang; Qingyao Hu; Jun Lu; Shijie Cui; Yaqing Gao; et al. (Science Bulletin, 2023)

Genetic variation reveals the enhanced microbial hyaluronan biosynthesis via atmospheric and room temperature plasma - Zhi-Yuan Yao; Jin-Song Gong; Yu-Ru Liu; Jia-Yu Jiang; Yue-Sheng Zhang; Chang Su; Heng Li; Chuan-Li Kang; Lei Liu; Zheng-Hong Xu; Jin-Song Shi (Carbohydrate Polymers, 2023)

Projections from the Prefrontal Cortex to Zona Incerta Mediate Fear Generalization - Kun Tong; Guang-Kai Bu; Si-Qi Jing; Tong Wu; Yu-Tong Song; Yue You; Le Liu; Yuan-Hao Chen; Jing-Ru Hao; Nan Sun; Can Gao (Neuroscience Bulletin, 2023)

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

Polybenzimidazole-reinforced polyethylene oxide-based polymer-in-salt electrolytes enabling excellent structural stability and superior electrochemical performance for lithium metal batteries - Lei Zou; Kun Shi; Honglei Liu; Yong Wu; Tao Xu; Qiang Wang; Zhangxian Chen; Zeheng Yang; Ru Song; Jianhui Su; Weixin Zhang (Chemical Engineering Journal, 2023)

Molybdenum carbide changes the abundance of antibiotic resistance genes and bacterial communities in bioelectrocatalytic systems treating wastewater contaminated by tetracycline - Yi Shao; Yu-Xiang Lu; Shi-Ru Gao; Bolun Xie; Xiao-Li Yang; Hai-Liang Song (Bioresource Technology Reports, 2023)

Effect of agricultural soil wind erosion on urban PM2.5 concentrations simulated by WRF-Chem and WEPS: A case study in Kaifeng, China - Haopeng Zhang; Hongquan Song; Xiaowei Wang; Yaobin Wang; Ruiqi Min; Minghui Qi; Xutong Ru; Tianqi Bai; Hua Xue (Chemosphere, 2023)

Machine learning based age-authentication assisted by chemo-kinetics: Case study of strong-flavor Chinese Baijiu - Qing-Ru Liu; Xiao-Juan Zhang; Lei Zheng; Lian-Jun Meng; Guang-Qian Liu; Ting Yang; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Cai-Hong Shen; Zheng-Hong Xu (Food Research International, 2023)

Remediating flooding paddy soils with schwertmannite greatly reduced arsenic accumulation in rice (Oryza sativa L.) but did not decrease the utilization efficiency of P fertilizer - Ru Wang; Yinglin Guo; Yang Song; Yuting Guo; Xiaomeng Wang; Quan Yuan; Zengping Ning; Chengshuai Liu; Lixiang Zhou; Guanyu Zheng (Environmental Pollution, 2023)

mRNA 3ʹ -UTR-mediate translational control through PAS and CPE in sheep oocyte - Chun-Ru Song; Ru-Jing Zhang; Fang-Rui Xue; Xiao-Jie Zhang; Xing-Yue Wang; Dui Sun; Kang Ding; Qi Yang; Xin-Yu Wang; Cheng-Guang Liang (Theriogenology, 2023)

A novel oxygen vacancies enriched Co Ni LDO catalyst activated peroxymonosulfate for the efficient degradation of tetracycline - Hao-Liang Jiang; Ming-Hui Li; Ling-Xi Zhao; Zhao-Xing Yan; Meng Xie; Jin-Ming Lin; Ru-Song Zhao (Journal of Water Process Engineering, 2023)

Magnetic ternary layered double hydroxides for efficient removal of 1-naphthalene acetic acid from waters: Adsorption behavior and mechanism - Ti-Bo Fang; Hua Xiao; Ling-Xi Zhao; Na Li; Ling-Yu Luan; Zhao-Xing Yan; Jin-Ming Lin; Ru-Song Zhao (Journal of Environmental Chemical Engineering, 2023)

Glycation of whey protein isolate and stachyose modulates their in vitro digestibility: Promising prebiotics as functional ingredients - Guang-yao Zhang; Cong Sun; Jing-ru Song; Wei-yi Jin; Yue Tang; Da-yong Zhou; Liang Song (Food Bioscience, 2023)

When things get MESI: The Manipulation Experiments Synthesis Initiative—A coordinated effort to synthesize terrestrial global change experiments - Kevin Van Sundert; Sebastian Leuzinger; Martin K.‐F. Bader; Scott X. Chang; Martin G. De Kauwe; Jeffrey S. Dukes; J. Adam Langley; Zilong Ma; Bertold Mariën; Simon Reynaert; Jingyi Ru; Jian Song; et al. (Global Change Biology, 2023)
Responses of the terrestrial biosphere to rapidly changing environmental conditions are a major source of uncertainty in climate projections. In an effort to reduce this uncertainty, a wide range of global change experiments have been conducted that mimic future conditions in terrestrial ecosystems, manipulating CO 2 , temperature, and nutrient and water availability. Syntheses of results across experiments provide a more general sense of ecosystem responses to global change, and help to discern the influence of background conditions such as climate and vegetation type in determining global change responses. Several independent syntheses of published data have yielded distinct databases for specific objectives. Such parallel, uncoordinated initiatives carry the risk of producing redundant data collection efforts and have led to contrasting outcomes without clarifying the underlying reason for divergence. These problems could be avoided by creating a publicly available, updatable, curated database. Here, we report on a global effort to collect and curate 57,089 treatment responses across 3644 manipulation experiments at 1145 sites, simulating elevated CO 2 , warming, nutrient addition, and precipitation changes. In the resulting Manipulation Experiments Synthesis Initiative (MESI) database, effects of experimental global change drivers on carbon and nutrient cycles are included, as well as ancillary data such as background climate, vegetation type, treatment magnitude, duration, and, unique to our database, measured soil properties. Our analysis of the database indicates that most experiments are short term (one or few growing seasons), conducted in the USA, Europe, or China, and that the most abundantly reported variable is aboveground biomass. We provide the most comprehensive multifactor global change database to date, enabling the research community to tackle open research questions, vital to global policymaking. The MESI database, freely accessible at doi.org/10.5281/zenodo.7153253 , opens new avenues for model evaluation and synthesis‐based understanding of how global change affects terrestrial biomes. We welcome contributions to the database on GitHub.

Overcompensation of ecosystem productivity following sustained extreme drought in a semiarid grassland - Jingyi Ru; Shiqiang Wan; Dafeng Hui; Jian Song (Ecology, 2023)
Drought events are projected to be more extreme and frequent in the future and have profound influences on the structure and functions of terrestrial ecosystems. Thus, better understanding the mechanisms of recovery is critical for predicting the future dynamics of terrestrial ecosystems. We performed a 7‐year field precipitation experiment to examine recovery of a grassland ecosystem from different magnitudes of sustained drought, from slight to extreme. The ecosystem was exposed to precipitation treatments in the first 3 years (2010–2012) and recovered during the last 4 years (2013–2016) without precipitation treatments. Overall, large reductions of aboveground net primary productivity (ANPP, −43.3%) and perennial forb biomass (−83.1%) were observed in the third year (2012) of extreme drought only. Nevertheless, ANPP fully recovered within 1 year after the drought treatments were terminated, and the rapid recovery was mainly due to increased soil total nitrogen and root biomass allocation after drought. Surprisingly, large increases of ANPP under the extreme drought treatment occurred during the recovery periods from 2013 to 2015 (+74.1, +88.5, and +119.8 g m −2 year −1 ) compared to the control. The overcompensation offset the extreme drought‐induced reduction of ANPP in the treatment years and was primarily ascribed to the enhanced biomass of perennial grasses (PG). Higher resistance to drought and fast resource acquisition strategy might drive the rapid recovery and expansion of PG. Our findings revealed the rapid recovery of grasslands and the critical role of community overcompensation in maintaining grassland ecosystem function and stability under future climate change scenarios.

Application of microbial-induced carbonate precipitation (MICP) techniques to remove heavy metal in the natural environment: A critical review - Amit Kumar; He-Wei Song; Saurabh Mishra; Wei Zhang; Yu-Ling Zhang; Qian-Ru Zhang; Zhi-Guo Yu (Chemosphere, 2023)

Room-temperature synthesis of nitrogen-rich conjugated microporous polymers for solid-phase extraction of trace synthetic musks - Ye-Fei Fan; Hai-Long Jiang; Xiang-Feng Chen; Na Li; Xiao-Li Wang; Jin-Ming Lin; Ru-Song Zhao (Food Chemistry, 2023)

Aggregating-agent-assisted surface-enhanced Raman spectroscopy–based detection of acrylamide in fried foods: A case study with potato chips - Zhi-hao Ye; Xiao-tong Chen; Hai-yan Zhu; Xiao-qian Liu; Wen-hui Deng; Wei Song; Da-xiang Li; Ru-yan Hou; Hui-mei Cai; Chuan-yi Peng (Food Chemistry, 2023)

Metallurgical performance and structural characteristics of cokes of hypercoal prepared from the mixture of low-rank coal and biomass residue - Jun Zhao; Hong Liu; Haochen Zhang; Xiaolin Song; Haibin Zuo; Guangwei Wang; Zhigao Xu; Ming Wu; Zhenyue Zhang; Ru'an Chi (Fuel, 2023)

Association between pyrethroid exposure and risk of depressive symptoms in the general US adults - Hui-ru Li; Xi-hang Fu; Ling-ling Song; Man-qiu Cen; Jing Wu (Environmental Science and Pollution Research, 2023)

Three-dimensional hydroxylated covalent organic frameworks for solid phase extraction of glucocorticoids in environmental water samples - Chuqing Liu; Guiju Xu; Baoyu Li; Xiaoli Wang; Jin-Ming Lin; Ru-Song Zhao (Analytica Chimica Acta, 2023)

Cryo-EM structures reveal the dynamic transformation of human alpha-2-macroglobulin working as a protease inhibitor - Xiaoxing Huang; Youwang Wang; Cong Yu; Hui Zhang; Qiang Ru; Xinxin Li; Kai Song; Min Zhou; Ping Zhu (Science China Life Sciences, 2022)

Nitrogen enrichment alters multiple dimensions of grassland functional stability via changing compositional stability - Qianna Xu; Xian Yang; Jian Song; Jingyi Ru; Jianyang Xia; Shaopeng Wang; Shiqiang Wan; Lin Jiang (Ecology Letters, 2022)
Anthropogenic nutrient enrichment is known to alter the composition and functioning of plant communities. However, how nutrient enrichment influences multiple dimensions of community‐ and ecosystem‐level stability remains poorly understood. Using data from a nitrogen (N) and phosphorus (P) addition experiment in a temperate semi‐arid grassland that experienced a natural drought, we show that N enrichment, not P enrichment, decreased grassland functional and compositional temporal stability, resistance and recovery but increased functional and compositional resilience. Compositional stability and species asynchrony, rather than species diversity, were identified as key determinants of all dimensions of grassland functional stability, except for recovery. Whereas grassland functional recovery was decoupled from compositional recovery, N enrichment altered other dimensions of functional stability primarily through changing their corresponding compositional stability dimensions. Our findings highlight the need to examine ecological stability at the community level for a more mechanistic understanding of ecosystem dynamics in the face of environmental change.

ACOT7 protects epidermal stem cells against lipid peroxidation - Guang Zhang; Jiaxu Ma; Zhenjie Wu; Guoqi Cao; Chunyan Liu; Ru Song; Rui Sun; Aoyu Chen; Yibing Wang; Siyuan Yin (In Vitro Cellular & Developmental Biology - Animal, 2022)
Epidermal stem cells (ESCs) are critical for skin regeneration and repair. Previous studies have shown that ESCs are susceptible to oxidative stress, which in turn leads to lipid peroxidation and affects skin repair. Our study aims to explore how ESCs resist lipid peroxidation. By performing proteomics analysis, we found that the expression of Acyl-CoA thioesterase 7 (ACOT7) was positively correlated with the concentration of transferrin. Overexpression adenovirus vectors of ACOT7 were constructed and transfected into ESCs. Levels of lipid peroxidation by flow cytometry, cell viabilities, and MDA levels were measured. The results revealed that ACOT7 could inhibit lipid peroxidation, reduce the level of malondialdehyde (MDA), and improve the survival rate of ESCs induced by H 2 O 2 , Erastin, and RSL3. Our data suggest that ACOT7 has an effect on protecting ESCs against iron-dependent lipid peroxidation.

Increased precipitation and nitrogen addition accelerate the temporal increase in soil respiration during 8‐year old‐field grassland succession - Jiajia Zhang; Jingyi Ru; Jian Song; Heng Li; Xiaoming Li; Yafei Ma; Zheng Li; Yuanfeng Hao; Zhensheng Chi; Dafeng Hui; Shiqiang Wan (Global Change Biology, 2022)
Ecological succession after disturbance plays a vital role in influencing ecosystem structure and functioning. However, how global change factors regulate ecosystem carbon (C) cycling in successional plant communities remains largely elusive. As part of an 8‐year (2012–2019) manipulative experiment, this study was designed to examine the responses of soil respiration and its heterotrophic component to simulated increases in precipitation and atmospheric nitrogen (N) deposition in an old‐field grassland undergoing secondary succession. Over the 8‐year experimental period, increased precipitation stimulated soil respiration by 11.6%, but did not affect soil heterotrophic respiration. Nitrogen addition increased both soil respiration (5.1%) and heterotrophic respiration (6.2%). Soil respiration and heterotrophic respiration linearly increased with time in the control plots, resulting from changes in soil moisture and shifts of plant community composition from grass–forb codominance to grass dominance in this old‐field grassland. Compared to the control, increased precipitation significantly strengthened the temporal increase in soil respiration through stimulating belowground net primary productivity. By contrast, N addition accelerated temporal increases in both soil respiration and its heterotrophic component by driving plant community shifts and thus stimulating soil organic C. Our findings indicate that increases in water and N availabilities may accelerate soil C release during old‐field grassland succession and reduce their potential positive impacts on soil C accumulation under future climate change scenarios.

A New Scheme for Capturing Global Conditional Nonlinear Optimal Perturbation - Siyuan Liu; Qi Shao; Wei Li; Guijun Han; Kangzhuang Liang; Yantian Gong; Ru Wang; Hanyu Liu; Song Hu (Journal of Marine Science and Engineering, 2022)
Conditional nonlinear optimal perturbation (CNOP) represents the initial perturbation that satisfies a certain physical constraint condition, and leads to a maximum prediction error at the moment of prediction. The CNOP method is a useful tool in studying atmosphere and ocean predictability problems. Generally, the optimization algorithm based on the gradient of the cost function to compute CNOP requires an initial guess. The traditional scheme randomly chooses the initial guess of CNOP within the constraint range and therefore this scheme is called RIG-CNOP. However, the RIG-CNOP scheme reduces the probability of capturing the global CNOP in many cases, such as the prediction model is strongly nonlinear or long-term prediction is performed, or multiple extreme values existed in the cost function. Considering the limitations of the RIG-CNOP scheme, we propose a new initial guess selection scheme. In this scheme, we first pre-analyze a series of random initial guesses, and then, an optimal initial guess is selected. The above process replaces the initial guess selection scheme in the traditional scheme, which is called PAIG-CNOP. Numerical experiments are conducted utilizing the Lorenz-63 model. Also, to compare the performance of the PAIG-CNOP method with the RIG-CNOP method in capturing global CNOP, the CNOP and the maximum cost function value (MCFV) obtained by the filtering method (FM) are used as benchmarks (this value is called FMMCFV in brief). The experimental results show that even the prediction model is strongly nonlinear or the prediction time is long, or the cost function has multiple extreme values, the PAIG-CNOP method can capture the global CNOP with a high probability. The results show that the PAIG-CNOP method has a higher probability of capturing the global CNOP than the RIG-CNOP method. In addition, we use an ensemble-based technique in the computation of gradients, thus avoiding the use of adjoint techniques in the maximization process. Due to the attractive features of the new method, the PAIG-CNOP method is an efficient and useful method for solving CNOP, it can be more easily applied to obtain the global CNOP of operational prediction models.

Soil moisture response to land use and topography across a semi-arid watershed: Implications for vegetation restoration on the Chinese Loess Plateau - Lu Xia; Ru-tian Bi; Xiao-yu Song; Wei Hu; Chun-juan Lyu; Xu Xi; Huai-you Li (Journal of Mountain Science, 2022)

Carbon, oxygen and strontium isotopes of the Mesoproterozoic Jixian System （1.6-1.4 Ga）in the southern margin of the North China Craton and the geological implications - Cong Tan; Yuanzheng Lu; Xin Li; Haonan Song; Dan Lv; Xueying Ma; Ru Fan; Shenghui Deng (International Geology Review, 2021)

Recent progress of oridonin and its derivatives for cancer therapy and drug resistance - Yong-Feng Guan; Xiu-Juan Liu; Xiao-Jing Pang; Wen-Bo Liu; Guang -Xi Yu; Yin -Ru Li; Yan-Bing Zhang; Jian Song; Sai-Yang Zhang (Medicinal Chemistry Research, 2021)

Genetic Analysis of ZNF Protein Family Members for Early-Onset Parkinson’s Disease in Chinese Population - Chun Yu Li; Ru Wei Ou; Yong Ping Chen; Xiao Jing Gu; Qian Qian Wei; Bei Cao; Ling Yu Zhang; Yan Bing Hou; Kun Cheng Liu; Xue Ping Chen; Wei Song; Bi Zhao; et al. (Molecular Neurobiology, 2021)

Marinifaba aquimaris gen. nov., sp. nov., a novel chitin‐degrading gammaproteobacterium in the family Alteromonadaceae isolated from seawater of the Mariana Trench - Xin Sui; Xiao-yan He; Ning-hua Liu; Yan-ru Dang; Qian-qian Cha; Mei-ling Sun; Chun-yang Li; Hui-hui Fu; Xiao-yan Song; Qi-long Qin; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

An Infrared Touch System for Automatic Behavior Monitoring - Qingqing Liu; Xing Yang; Ru Song; Junying Su; Moxuan Luo; Jinling Zhong; Liping Wang (Neuroscience Bulletin, 2021)
Key requirements of successful animal behavior research in the laboratory are robustness, objectivity, and high throughput, which apply to both the recording and analysis of behavior. Many automatic methods of monitoring animal behavior meet these requirements. However, they usually depend on high-performing hardware and sophisticated software, which may be expensive. Here, we describe an automatic infrared behavior-monitor (AIBM) system based on an infrared touchscreen frame. Using this, animal positions can be recorded and used for further behavioral analysis by any PC supporting touch events. This system detects animal behavior in real time and gives closed-loop feedback using relatively low computing resources and simple algorithms. The AIBM system automatically records and analyzes multiple types of animal behavior in a highly efficient, unbiased, and low-cost manner.

New 40Ar/39Ar and (U-Th)/He dating for the Zhunuo porphyry Cu deposit, Gangdese belt, southern Tibet: implications for pulsed magmatic-hydrothermal processes and ore exhumation and preservation - Xiang Sun; Cheng-Biao Leng; Pete Hollings; Qing-Jie Song; Ru-Yue Li; Xiu-Quan Wan (Mineralium Deposita, 2021)

Molecular epidemiological characteristics of echovirus 6 in mainland China: extensive circulation of genotype F from 2007 to 2018 - Wenjun Cheng; Tianjiao Ji; Shuaifeng Zhou; Yong Shi; Lili Jiang; Yong Zhang; Dongmei Yan; Qian Yang; Yang Song; Ru Cai; Wenbo Xu (Archives of Virology, 2021)
Echovirus 6 (E6) is associated with various clinical diseases and is frequently detected in environmental sewage. Despite its high prevalence in humans and the environment, little is known about its molecular phylogeography in mainland China. In this study, 114 of 21,539 (0.53%) clinical specimens from hand, foot, and mouth disease (HFMD) cases collected between 2007 and 2018 were positive for E6. The complete VP1 sequences of 87 representative E6 strains, including 24 strains from this study, were used to investigate the evolutionary genetic characteristics and geographical spread of E6 strains. Phylogenetic analysis based on VP1 nucleotide sequence divergence showed that, globally, E6 strains can be grouped into six genotypes, designated A to F. Chinese E6 strains collected between 1988 and 2018 were found to belong to genotypes C, E, and F, with genotype F being predominant from 2007 to 2018. There was no significant difference in the geographical distribution of each genotype. The evolutionary rate of E6 was estimated to be 3.631 × 10 -3 substitutions site -1 year -1 (95% highest posterior density [HPD]: 3.2406 × 10 -3 -4.031 × 10 -3 substitutions site -1 year -1 ) by Bayesian MCMC analysis. The most recent common ancestor of the E6 genotypes was traced back to 1863, whereas their common ancestor in China was traced back to around 1962. A small genetic shift was detected in the Chinese E6 population size in 2009 according to Bayesian skyline analysis, which indicated that there might have been an epidemic around that year.

Genetic Analysis of Prosaposin, the Lysosomal Storage Disorder Gene in Parkinson’s Disease - Yong-Ping Chen; Xiao-Jing Gu; Ru-Wei Ou; Ling-Yu Zhang; Yan-Bing Hou; Kun-Cheng Liu; Bei Cao; Qian-Qian Wei; Wei Song; Bi Zhao; Ying Wu; Jing-Qiu Cheng; et al. (Molecular Neurobiology, 2021)

Effects of Grazing, Wind Erosion, and Dust Deposition on Plant Community Composition and Structure in a Temperate Steppe - Mengmei Zheng; Jian Song; Jingyi Ru; Zhenxing Zhou; Mingxing Zhong; Lin Jiang; Dafeng Hui; Shiqiang Wan (Ecosystems, 2021)

Nonadditive and Legacy Effects of Spring and Autumn Warming on Soil Respiration in an Old-Field Grassland - Shijie Ning; Jian Song; Jingyi Ru; Zhenxing Zhou; Jiajia Zhang; Xianghui Liu; Yan Hui; Yafei Ma; Shiqiang Wan (Ecosystems, 2021)

Content and health risk assessment of heavy metals and polybrominated diphenyl ethers in fish from Songhua Lake (Jilin City), China - Mengnan Shen; Chunyu Kang; Tiehong Song; Hai Lu; Yuehong Wang; Bowen Yu; Ru Wang; Jie Cheng (Environmental Science and Pollution Research, 2020)

Low Serum Uric Acid Levels Promote Hypertensive Intracerebral Hemorrhage by Disrupting the Smooth Muscle Cell-Elastin Contractile Unit and Upregulating the Erk1/2-MMP Axis - Ning Xiao; Tian-long Liu; Hao Li; Hao-chen Xu; Jing Ge; Hong-yan Wen; Cong-xia Bai; Li Song; Ying-ying Sun; Yin-hui Zhang; Ru-tai Hui; Wei-hua Song; et al. (Translational Stroke Research, 2020)

Impaired Parahippocampal Gyrus–Orbitofrontal Cortex Circuit Associated with Visuospatial Memory Deficit as a Potential Biomarker and Interventional Approach for Alzheimer Disease - Lin Zhu; Zan Wang; Zhanhong Du; Xinyang Qi; Hao Shu; Duan Liu; Fan Su; Qing Ye; Xuemei Liu; Zheng Zhou; Yongqiang Tang; Ru Song; et al. (Neuroscience Bulletin, 2020)

Pasture degradation impact on soil carbon and nitrogen fractions of alpine meadow in a Tibetan permafrost region - Zi-Qiang Yuan; Qing-Bai Wu; Xin Song; Xiao-Jin Jiang; Si-Ru Gao; Qing-Feng Wang; Guo-Yu Li (Journal of Soils and Sediments, 2020)

Collagen-binding basic fibroblast growth factor improves functional remodeling of scarred endometrium in uterine infertile women: a pilot study - Peipei Jiang; Xiaoqiu Tang; Huiyan Wang; Chenyan Dai; Jing Su; Hui Zhu; Minmin Song; Jingyu Liu; Ziqing Nan; Tong Ru; Yaling Li; Jingmei Wang; et al. (Science China Life Sciences, 2019)

Asymmetric responses of plant community structure and composition to precipitation variabilities in a semi-arid steppe - Mingxing Zhong; Jian Song; Zhenxing Zhou; Jingyi Ru; Mengmei Zheng; Ying Li; Dafeng Hui; Shiqiang Wan (Oecologia, 2019)

Hepatitis C virus 3b strains in injection drug users in Guangdong Province, China, may have originated in Yunnan Province - Min Wang; Qiao Liao; Ru Xu; Dandan Song; Jieting Huang; Qingzhu You; Zhengang Shan; Ke Huang; Xia Rong; Yongshui Fu (Archives of Virology, 2019)

High-degree and broad-spectrum resistance mediated by a combination of NIb siRNA and miRNA suppresses replication of necrotic and common strains of potato virus Y - Ru Yu; Caixia Chen; Weilin Cao; Hongmei Liu; Shumei Zhou; Yunzhi Song; Changxiang Zhu (Archives of Virology, 2018)

Investigating the composition characteristics of dissolved and particulate/colloidal organic matter in effluent-dominated stream using fluorescence spectroscopy combined with multivariable analysis - Min-Da Yu; Xiao-Song He; Bei-Dou Xi; Ru-Tai Gao; Xian-Wei Zhao; Hui Zhang; Cai-Hong Huang; Wenbing Tan (Environmental Science and Pollution Research, 2018)

Characteristic differences in essential oil composition of six Zanthoxylum bungeanum Maxim. (Rutaceae) cultivars and their biological significance - Shu-ming Liu; Shi-jun Wang; Si-yao Song; Yong Zou; Jun-ru Wang; Bing-yin Sun (Journal of Zhejiang University-SCIENCE B, 2017)

Altered Resting-State Signals in Patients with Acute Stroke In or Under the Thalamus - Lijun Chen; Chuanfu Li; Jian Zhai; Anqin Wang; Qin Song; Ying Liu; Ru Ma; Long Han; Yamikani Ndasauka; Xiaoming Li; Hai Li; Xiaochu Zhang (Neuroscience Bulletin, 2016)

A new method for the stability analysis of geosynthetic-reinforced slopes - Fei Song; Ru-yi Chen; Li-qiu Ma; Geng-ren Cao (Journal of Mountain Science, 2016)

Norovirus outbreaks in Fengtai District, Beijing, China, 2014 - Jin-Song Li; Meng Qin; Xiao-Gen Dong; Jun-Yong Yang; Xiao-Xin Yang; Xiu-xia Wei; Zhao-e Wang; Hui-ru Feng; Qin-rui Wu; Ruo-xi Li; Jie Li; Zhao-Jun Duan (Archives of Virology, 2016)

A Waterborne Gastroenteritis Outbreak Caused by Norovirus GII.17 in a Hotel, Hebei, China, December 2014 - Meng Qin; Xiao-Gen Dong; Yan-Yan Jing; Xiu-xia Wei; Zhao-E Wang; Hui-Ru Feng; Hong Yu; Jin-Song Li; Jie Li (Food and Environmental Virology, 2016)

Functional expression of human serum albumin-tandem thrombopoietin mimetic peptide fusion protein as a novel thrombopoietin analog in Pichia pastoris - Meizhu Wang; Dejuan Zhi; Jun Xian; Yi Ru; Suzhen Wei; Na Wang; Yiyao Liu; Haiqing Wang; Yuejuan Pei; Meijuan Song; Yang Li; Hongyu Li (Biotechnology Letters, 2016)

Neuroprotection of Sevoflurane Against Ischemia/Reperfusion-Induced Brain Injury Through Inhibiting JNK3/Caspase-3 by Enhancing Akt Signaling Pathway - Xiang-Ru Wen; Yan-Yan Fu; Hong-Zhi Liu; Jian Wu; Xiao-Ping Shao; Xun-Bao Zhang; Man Tang; Yue Shi; Kai Ma; Fang Zhang; Yi-Wen Wang; Hui Tang; et al. (Molecular Neurobiology, 2016)

The impact of different forest types on phytolith-occluded carbon accumulation in subtropical forest soils - Xiaodong Zhang; Zhaoliang Song; Kim McGrouther; Jianwu Li; Zimin Li; Ning Ru; Hailong Wang (Journal of Soils and Sediments, 2016)

Dormancy release of Cotinus coggygria seeds under a pre-cold moist stratification: an endogenous abscisic acid/gibberellic acid and comparative proteomic analysis - Zhi Jun Deng; Xiao Fang Hu; Xun Ru Ai; Lan Yao; Shi Ming Deng; Xin Pu; Song Quan Song (New Forests, 2016)

Di-(2-ethylhexyl) phthalate accelerates atherosclerosis in apolipoprotein E-deficient mice - Jin-Feng Zhao; Sheng-Huang Hsiao; Ming-Hua Hsu; Kuan-Chuan Pao; Yu Ru Kou; Song-Kun Shyue; Tzong-Shyuan Lee (Archives of Toxicology, 2016)

Invasive fungal infection in allogeneic hematopoietic stem cell transplant recipients: single center experiences of 12 years - Ji-min Shi; Xu-ying Pei; Yi Luo; Ya-min Tan; Ru-xiu Tie; Jing-song He; Wei-yan Zheng; Jie Zhang; Zhen Cai; Mao-fang Lin; He Huang (Journal of Zhejiang University-SCIENCE B, 2015)

Efficient secretory production of CotA-laccase and its application in the decolorization and detoxification of industrial textile wastewater - Zheng-Bing Guan; Yan Shui; Chen-Meng Song; Ning Zhang; Yu-Jie Cai; Xiang-Ru Liao (Environmental Science and Pollution Research, 2015)

Using fluorescence spectroscopy coupled with chemometric analysis to investigate the origin, composition, and dynamics of dissolved organic matter in leachate-polluted groundwater - Xiao-Song He; Bei-Dou Xi; Ru-Tai Gao; Lei Wang; Yan Ma; Dong-Yu Cui; Wen-Bing Tan (Environmental Science and Pollution Research, 2015)

Biochemical Properties and Stability of Antioxidative Activity of Half-Fin Anchovy ( Setipinna taty ) Fermented Product - Ru Song; Rongbian Wei; Hongyu Luo (Journal of Aquatic Food Product Technology, 2015)

Influence of pH, inorganic anions, and dissolved organic matter on the photolysis of antimicrobial triclocarban in aqueous systems under simulated sunlight irradiation - Shi-Ling Ding; Xi-Kui Wang; Wen-Qiang Jiang; Ru-Song Zhao; Ting-Ting Shen; Chen Wang; Xia Wang (Environmental Science and Pollution Research, 2015)

Distribution and ecological risk assessment of HCHs and DDTs in surface seawater and sediment of the mariculture area of Jincheng Bay, China - Yanbing Hu; Shan Sun; Xiukai Song; Jianxin Ma; Shaoguo Ru (Journal of Ocean University of China, 2015)

The Recovery Process of Mice Tracheal Epithelium Injured by 5-FU and Its Microarray Analysis - Jing-Ru Zhang; Nan Song; Xin-Shan Jia; Shan-Liang Sun; Xiao-Bo Ma; En-Hua Wang (Cell Biochemistry and Biophysics, 2014)

Structure–activity relationships of anthocyanidin glycosylation - Chang Ling Zhao; Zhong Jian Chen; Xue Song Bai; Can Ding; Ting Ju Long; Fu Gang Wei; Kang Ru Miao (Molecular Diversity, 2014)

A novel deletion mutation of the ADAR1 gene in a Chinese patient with dyschromatosis symmetrica hereditaria - WEI-WEI LI; QIU-YUE WU; NA LI; DE-QUAN DENG; RU-SONG ZHANG; YING-XIA CUI; XIAO-JUN LI; XIN-YI XIA (Journal of Genetics, 2014)

Nuclear factor-κB signaling pathway is involved in phospholipase Cε-regulated proliferation in human renal cell carcinoma cells - Hong-fei Du; Li-ping Ou; Xue-dong Song; Yan-ru Fan; Xue Yang; Bing Tan; Zhen Quan; Chun-Li Luo; Xiao-hou Wu (Molecular and Cellular Biochemistry, 2014)

Development and Characterisation of Ursolic Acid Nanocrystals Without Stabiliser Having Improved Dissolution Rate and In Vitro Anticancer Activity - Ju Song; Yancai Wang; Yuelin Song; Hokman Chan; Chao Bi; Xiao Yang; Ru Yan; Yitao Wang; Ying Zheng (AAPS PharmSciTech, 2014)

Two new cytotoxic iridoid esters from the rhizomes and roots of Patrinia heterophylla Bunge - Bo Yang; Ru-Bin Cheng; Yi-Qi Wang; Li Shen; Ru-Song Zhang (Natural Product Research, 2013)

Development of thermo-sensitive cytoplasmic male sterile (TCMS) lines of wheat characterized by complete male sterility at lower-temperatures and partially restored fertility at higher-temperatures - Xi Yue Song; Ling Li Zhang; Jun Li Zeng; Huan Huan Qian; Hong Bin Li; Bei Ru He (Euphytica, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Photodegradation of the antimicrobial triclocarban in aqueous systems under ultraviolet radiation - Shi-Ling Ding; Xi-Kui Wang; Wen-Qiang Jiang; Xia Meng; Ru-Song Zhao; Chen Wang; Xia Wang (Environmental Science and Pollution Research, 2013)

Imposex effects on the veined rapa whelk (Rapana venosa) in Bohai Bay, China - Li-hui An; Yanqiang Zhang; Shuang-shuang Song; Yue Liu; Zi-cheng Li; Hao Chen; Xing-ru Zhao; Kun Lei; Junmin Gao; Bing-hui Zheng (Ecotoxicology, 2013)

Analysis of average standardized SSR allele size supports domestication of soybean along the Yellow River - Ying-hui Li; Chen Zhang; Marinus J. M. Smulders; Wei Li; Yan-song Ma; Qu Xu; Ru-zhen Chang; Li-juan Qiu (Genetic Resources and Crop Evolution, 2013)

Tomographic inversion for microseismic source parameters in mining - Hua-Xiang Miao; Fu-Xing Jiang; Xue-Juan Song; Shu-Hua Yang; Jun-Ru Jiao (Applied Geophysics, 2012)

Automatically positioning microseismic sources in mining by the stereo tomographic method using full wavefields - Hua-Xiang Miao; Fu-Xing Jiang; Xue-Juan Song; Jian-Yong Song; Shu-Hua Yang; Jun-Ru Jiao (Applied Geophysics, 2012)

Evaluation of seed storage-protein gene 5′ untranslated regions in enhancing gene expression in transgenic rice seed - Wen Xian Liu; Hua Liang Liu; Zhi Jian Chai; Xiu Ping Xu; Yan Ru Song; Le Qing Qu (Theoretical and Applied Genetics, 2010)

Livin abrogates apoptosis of SPC-A1 cell by regulating JNKI signaling pathway - Yu-Sheng Chen; Hong-Ru Li; Ming Lin; Gang Chen; Bao-Song Xie; Neng-Luan Xu; Li-Fang Lin (Molecular Biology Reports, 2010)

Analysis of the genetic diversity in Saccharum spontaneum L. accessions from Guangxi Province of China with RAPD-PCR - Ge-min Zhang; Yang-Rui Li; Wei-Zhong He; Hong He; Xi-Hui Liu; Huan-Zhong Song; Hai-Bin Liu; Ru-Cai Zhu; Wei-Kuan Fang (Sugar Tech, 2010)

cDNA, genomic sequence cloning and overexpression of ribosomal protein S25 gene (RPS25) from the Giant Panda - Yan-zhe Hao; Wan-ru Hou; Yi-ling Hou; Yu-jie Du; Tian Zhang; Zheng-song Peng (Molecular Biology Reports, 2009)

High frequency plant regeneration following abnormal shoot organogenesis in the medicinal tree Hovenia dulcis - Mi Jin Jeong; Hyun Jin Song; Dong Jin Park; Ji Yun Min; Jin Seong Jo; Bo Min Kim; Hak Gon Kim; Yong Duck Kim; Ru Mi Kim; Chandrakant S. Karigar; Myung Suk Choi (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

Identification of Inonotus obliquus and Analysis of Antioxidation and Antitumor Activities of Polysaccharides - Yana Song; Jing Hui; Wei Kou; Ru Xin; Fei Jia; Ning Wang; Fengqing Hu; Huili Zhang; Hongsheng Liu (Current Microbiology, 2008)

Studies on the factors affecting the growth and hemolytic activity of Anabaena variabilis - Wei Wang; Xiu-Kai Song; Shao-Guo Ru (Journal of Applied Phycology, 2007)

Nematicidal Resorcylides from the Aquatic Fungus Caryospora callicarpa YMF1.01026 - Jinyan Dong; Yanhui Zhu; Hongchuan Song; Ru Li; Hongping He; Haiyang Liu; Rong Huang; Yongping Zhou; Le Wang; Yi Cao; Keqin Zhang (Journal of Chemical Ecology, 2007)

TransgenicLycium barbarum L. Established as HIV capsid protein expression system - Guo-Li Du; Chang-Zheng Song; Geng-Lin Zhang; Xiao-Guang Sun; Dan-Ru Liu (Plant Molecular Biology Reporter, 2005)

Sustainable development of marine economy in China - Yao-guang Zhang; Li-jing Dong; Jun Yang; Sheng-yun Wang; Xin-ru Song (Chinese Geographical Science, 2004)

Cytoplasmic composition in Pinus densata and population establishment of the diploid hybrid pine - Bao‐Hua Song; Xiao‐Quan Wang; Xiao‐Ru Wang; Kai‐Yu Ding; De‐Yuan Hong (Molecular Ecology, 2003)
Sequence and restriction site analyses of the paternally inherited chloroplast rbc L gene and maternally inherited mitochondrial nad 1 fragments from the same set of populations and individuals were used to investigate cytoplasmic composition and population establishment of Pinus densata , a diploid pine that originated through hybridization between P . tabuliformis and P . yunnanensis . Two variable sites and three chlorotypes (TT, TC and GC) were detected on the rbc L gene of the three pines. P . densata harboured the three chlorotypes, two of which (TT, GC) were characteristic of the parental species, respectively. The third chlorotype (TC) was distributed extensively in seven of the 10 P . densata populations analysed, and might represent a mutation type or have been derived from an extinct parent. The distribution of chlorotypes, together with that of mitotypes, indicated that significant founder effect and backcross happened during the population establishment of the hybrid pine. P . tabuliformis and P . yunnanensis had acted as both mother and father donors, i.e. bi‐directional gene flow existed between the two parental species in the past. Population differentiation of P . densata is high, as detected from the cytoplasmic genomes: G ST = 0.533 for cpDNA and G ST = 0.905 for mtDNA. The differences in cytoplasmic composition among the hybrid populations suggest that the local populations have undergone different evolutionary histories.

Maternal lineages of Pinus densata , a diploid hybrid - Bao‐Hua Song; Xiao‐Quan Wang; Xiao‐Ru Wang; Lan‐Ju Sun; De‐Yuan Hong; Pei‐Hao Peng (Molecular Ecology, 2002)
Previous morphological, allozyme and chloroplast DNA data have suggested that Pinus densata originated through hybridization between P . tabuliformi s and P . yunnanensis . In the present study, sequence and restriction site analyses of maternally inherited mitochondrial nad 1 intron were used to detect variation patterns in 19 populations of P . tabuliformis , P . yunnanensis and P . densata . A total of three mitotypes (A, B, C) were detected. All but one of the populations of P . yunnanensis possessed mitotype B while all populations of P . tabuliformis had mitotype A. Pinus densata populations, on the other hand, harboured both mitotypes A and B, which are characteristic of P . tabuliformis and P . yunnanensis , respectively . This result gives strong additional evidence supporting the hybrid origin of this diploid pine. The distribution of mitotypes indicated very different mating compositions and evolutionary history among P . densata populations. It seems that local founder populations and backcrosses may have played important roles in the early establishment of P . densata populations. The uplift of the Tibetan Plateau had a significant impact on the distribution of maternal lineages of P . densata populations.

Differential expression of RAB5A in human lung adenocarcinoma cells with different metastasis potential - Li Yu; Feng Hui-chen; Yu Chen; Rong Zou; Song Yan; Liu Chun-xiang; Wang Wu-ru; Pu Li (Clinical & Experimental Metastasis, 1999)